Study on Strength Test and Application of Lime Soil in Pavement Base Modified by Soda Residue - Hui Li; Shengxue Zhu; Wei Yin; Zhiling Zhu; Kun Zhang; Xiaomin Bai; Dandan Liu; Yiting Tang (Advances in Civil Engineering)
To solve the difficult problems of large-scale utilization of solid waste soda residue (SR) as a resource and reduce the cost of road building materials, the technical idea of using SR instead of part of lime to prepare lime soil of pavement base was put forward. Through laboratory tests, the basic characteristics of SR and the optimum moisture content and maximum dry density of soda residue lime soil (SRLS) under different proportioning conditions were tested. The test results showed that (1) with the change of SR content in the range of 0%–12%, the optimum moisture content of SRLS showed the change law of first increasing and then decreasing, but the change range was small; (2) the UCS of SRLS gradually increased with the extension of curing age, with the strength increasing faster in the early stage and slower in the later stage. The UCS of SRLS with SR content in the range of 0%–12% shows the law of first increasing and then decreasing, and the UCS value was the highest when the content of SR is 3%. Compared to the control group, the increase in the amplitude of UCS is as high as 34.6%; (3) appropriate content of SR will increase the gelation of C-S-H and N-A-S-H, and at the same time generated hydrated calcium sulfate and other cementitious materials, enhancing the cementation and strength of SRLS. However, when the content of SR is too much, the excess SR will not participate in hydration reaction even reduce the strength of lime soil. The cost of road materials per kilometer in the test section of SRLS base can be saved by 164,000 yuan, and the treatment cost per ton of SR in alkali factory can be reduced by about 80 yuan. The research results have remarkable economic, technical, and social benefits, which can provide technical reference for large-scale recycling of solid waste SR.